2020
DOI: 10.31665/jfb.2020.11237
|View full text |Cite
|
Sign up to set email alerts
|

Pytochemical profile and antioxidant activity of chiltepin chili ( Capsicum annuum var. glabriusculum), Sonora, Mexico

Abstract: The effect of processing on potential changes of antioxidant activity (DPPH and ABTS), total phenolic content (TPC) and total flavonoids (FLAV) of feijoa pulp during storage was investigated. In addition, possible modifications in the phenolic composition of the pulp. The pulp was subjected to refrigeration (control, 5 °C), pasteurization (85 °C/5 min) and irradiation (2.0 kGy). TPC, FLAV, DPPH and ABTS were measured during 28 days, whereas the identification and quantification of phenolic compounds were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Chili is a plant that generally gives a spicy taste to food consumed by humans (SAHID et al, 2020). Behind its spiciness, chili has many secondary metabolites compounds that can potentially be developed including phenolic compounds (MORENO et al, 2018;ANJOS et al, 2022), flavonoids (VAZQUEZ-FlORES et al, 2020), antioxidants (AlAM et al, 2018, and even α-glucosidase inhibitory activities (NANOK & SANSENyA, 2019). α-glucosidase inhibitors are enzymes that function to inhibit the absorption of sugar in the blood (STEFANO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Chili is a plant that generally gives a spicy taste to food consumed by humans (SAHID et al, 2020). Behind its spiciness, chili has many secondary metabolites compounds that can potentially be developed including phenolic compounds (MORENO et al, 2018;ANJOS et al, 2022), flavonoids (VAZQUEZ-FlORES et al, 2020), antioxidants (AlAM et al, 2018, and even α-glucosidase inhibitory activities (NANOK & SANSENyA, 2019). α-glucosidase inhibitors are enzymes that function to inhibit the absorption of sugar in the blood (STEFANO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Cumpas and Sahuaripa chilies, ecotypes of piquin chili, showed levels with significant differences of β-carotene on mature chilies, with 6.03 and 5.70 mg per gram for DW, respectively. Both chilies were from Sonora State (northwest of Mexico) and were grown under greenhouse conditions ( 34 ). Two ecotypes of piquin chili from Tabasco State (southeastern Mexico) showed significant differences between carotenoid contents in ripe and unripe fruits.…”
Section: Carotenoidsmentioning
confidence: 99%
“…The number of capsaicinoids could be maintained without variation when the growth conditions are not so drastic or long-lasting as to impact the accumulation of these metabolites in the fruit ( 64 ). However, the content of total capsaicinoids has been reported with differences according to the degree of ripening under controlled conditions, with 1.41 and 1.68 mg g −1 DW in the immature state and 8.59–8.73 mg g −1 DW in mature fruits of the Sahuaripa and Cumpas lines, respectively ( 34 ). The analysis of ripe fruits of wild piquin chilis from Tamaulipas showed that the contents of total capsaicinoids were statistically different and showed differences among ecotypes in the same municipality ( 18 , 65 ).…”
Section: Capsaicinoidsmentioning
confidence: 99%
“…glabriusculum (Dunal) Heiser and Pickergil], which is widely distributed from Peru to the Southwestern United States. Its fruit has great relevance in Mexico due to its high market demand (Cano-Vázquez et al, 2015) because of its rich, aromatic profile (Mares-Quiñones and Valiente-Banuet, 2019), high antioxidant capacity, and high phenol, flavonoid, capsaicinoid, capsinoid, carotenoid, tocopherol, tocotrienol, and ascorbic acid content (Hayano-Kanashiro et al, 2016;Quintero et al, 2018;Vazquez-Flores et al, 2020). This C3-type plant is characterized by its shrub-like wild growth, reaching heights of 55-150 cm; compact, berry-like, spherical or ovoid fruit (0.87-1.68 cm in length, 0.45-0.81 cm in diameter, 0.20-0.55 g in weight, and 0.45-0.82 mL by volume); 2.5-3.0-mm hard-coated seed, and maturity time of 6-10 months (Hayano-Kanashiro et al, 2016;Mares-Quiñones and Valiente-Banuet, 2019;Beltrán-Burboa et al, 2020;Cano-González et al, 2021).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%